Structure of achievement motivation dispositions in elite and non-elite track and field athletes - Pietrzak, A.; Tokarz, A. (Physical Culture and Sport. Studies and Research, 2019)
Achievement motivation is a distinguishing disposition in elite and non-elite athletes. Implicit theories and competence perception influence the types of achievement goals and constitute separate achievement motivation dispositions. The context of sport promotes various achievement goals and implicit theories about athletic competence. For this reason, scientific research should focus on the intrapersonal profiles of achievement motivation dispositions (achievement goals, implicit theories, and competence perception) instead of specifying only one of them. This study explores differences between elite and non-elite athletes in terms of intrapersonal profiles of achievement motivation dispositions. 54 elite and 50 non-elite track and field athletes took part in the study. The results suggest that athletes tend to perceive their competence accurately. Cluster analysis of the studied dispositions was conducted. The clusters present sets of achievement dispositions that vary in intensity. Moreover, the results present trends of the differences between elite and non-elite athletes in two of the three clusters obtained in the study.